Pelatihan Strategi Ice Breaking sebagai Solusi Meningkatkan Keaktifan Santri Introvert dalam Belajar Bahasa Arab - Ahmadi, Ruli; Sucahyo, Nurwa; Hamzah, Amir; Jannah, Raudatul; Puspita, Mira (Lembaga Publikasi Ilmiah Nusantara, 2025)
Ice-breaking strategy training is conducted to enhance the participation of introverted students in Arabic language learning at Islamic boarding schools (pondok pesantren). This initiative aims to assist teachers in creating a more inclusive and interactive classroom environment, allowing introverted students to feel more comfortable and confident in engaging with the learning process. The implementation method begins with identifying needs and preparing training materials, followed by the development of training content and conducting workshops for teachers. After the training, teachers apply ice-breaking techniques in the classroom, which are then evaluated to measure their impact on student participation. The results indicate that ice-breaking techniques effectively improve interaction and engagement among introverted students. Most previously passive students began to participate more actively in discussions and classroom activities. Teachers also reported improvements in classroom management and student involvement in Arabic language lessons. Evaluations showed a significant increase in the participation of introverted students, accompanied by an improvement in their comprehension of the material. In conclusion, this training has proven effective in enhancing the engagement of introverted students and positively impacting Arabic language teaching in Islamic boarding schools. Therefore, the application of ice-breaking techniques can be expanded to other institutions to foster a more inclusive and interactive learning environment.